High North scenarios and subnational realities: policies and practices in the Norwegian/Russian border zone - Haugseth, Peter (Arctic and North, 2018)
Source at https://doi.org/10.17238/issn2221-2698.2018.33.137 . As the world was becoming more interdependent, with increased global awareness of the north-ernmost parts of the world, both the Norwegian and Russian governments showed more political commit-ment to and interest in new forms of region-building and development in the High North from 2006 and onwards. Today, more than ten years later, many regional changes are evident in the Norwegian-Russian border zone, as a consequence of expanded people-to-people contacts in the Barents Euro-Arctic Region (BEAR). In this peripheral border area between two national states, villages and cities have become more open, both sociologically and legally for increased cross border cooperation (CBC) and networking. In this article I will take stock of some of these borderland openings following on from the consequence of the two nations’ rising levels of interest in the High North. It explores the ways in which (inter-)national policy-making and state-substate interactions ultimately altered centre-periphery dynamics. This article has based its approach to understanding the interplay of domestic and foreign policy instruments on the ‘substate diplomacy’ literature, which argues that increased state-substate interactions constitute an efficient in-strument for extending cooperation beyond national state borders. The efficiency of regionally driven sub-state interactions is discussed from an empirical perspective. The present study analyses various High North development contexts and discourses (effective from 2008) in the Arctic borderland between Norway and Russia. The new political commitments presented in state-level official documents (the branding of the High North) envisioned a transference of new industrial-economic high tech scenarios from state to local level. These scenarios included new borderland visa regimes, co-existing with cross-border forums invest-ments in improvements of roads, infrastructure, and transport rationalisations. The present article briefly ...